Histoire des croisades - Michaud, Joseph François, 1767-1839. (Bruxelles)
10 c., 5 c.te (1. c. 210 s. ; 2. c. 207 s., [1] katlı sayfa harita ; 3. c. 220 s., [1] katlı sayfa harita ; 4. c. 252 s., [1] katlı sayfa harita ; 5. c. 227 s., [1] katlı sayfa harita ; 6. c. 240 s., [1] katlı sayfa harita ; 7. c. 242 s. ; 8. c. 232 s. ; 9. c. 315 s. ; 10. c. 273 s.)